Race, excess suspicion, and larceny in Upstate NY - Massey, Sean G. (Criminal justice studies, 2022)
Archival crime data collected by a police agency in Upstate New York from 2008 to 2015; outcome, sentencing, and incarceration data collected by the New York State’s Department of Criminal Justice Statistics; and demographic data collected by the U.S. Census were analyzed to explore how a suspect’s race and sex affect the investigation, prosecution, conviction, and sentencing in larceny cases. Results suggest that Black men were more likely to be the targets of excess suspicion, less likely to be granted leniency by prosecutors, no more likely to be convicted, but, if convicted, more likely to be incarcerated than White men.